"The post-antibiotic apocalypse" and the "war on superbugs": catastrophe discourse in microbiology, its rhetorical form and political function - Nerlich, Brigitte; James, Richard (Sage, 2009)
Discourses evoking an antibiotic apocalypse and a war on superbugs are emerging just at a time when so-called "catastrophe discourses" are undergoing critical and reflexive scrutiny in the context of global warming and climate change. This article combines insights from social science research into climate change discourses with applied metaphor research based on recent advances in cognitive linguistics, especially with relation to "discourse metaphors." It traces the emergence of a new apocalyptic discourse in microbiology and health care, examines its rhetorical and political function and discusses its advantages and disadvantages. It contains a reply by the author of the central discourse metaphor, "the post-antibiotic apocalypse," examined in the article.